Group Discussion As a Technique for teaching speaking for the tenth grade students in MAN Pinrang - EKA PURWANTI (Journal of Applied Linguistics, 2022)
Discussion is one of alternatives technique to help students to formulate their ideas and learn to communicate to the others. The group discussion could be a technique which might be worthy for students, because group discussion is a way where the students have opportunity to express their thinkings to discuss a certain subject, and share information. They can propose arguments, agreements, or disagreements to a topic, and they can also interchange their ideas, feelings, and experiences, and it gives students chances to speak. In this study is aimed to find out the effectiveness group discussion technique for teaching speaking for the tenth grade students in MAN Pinrang in Academic Year 2018/2019. This study was conducted at MAN Pinrang from July 17th, 2018 to August 7th, 2018. The population of this study was the whole tenth grade students which consist of 280 students, whereas the sample was 64 students which were chosen by random sampling technique. In collecting the data, the writer used oral test to measure the students speaking skill and it is administered twice, namely pre-test and post-test, then the data was analyzed by using SPSS. From the descriptive analysis, it was known that before the treatment the ability of both groups was relatively the same. The two group homogenous, before the treatment began because there was only a slight difference in result between the experimental group and control group. After receiving the different treatments, the result of the experimental group was better than of control group. Based on the statistical analysis, in can be seen that sig (2 tailed) 0,001 < 0,005 it means that there is a development after treated to the students’ speaking ability. From the result above, it can inferred that the group discussion as a technique for teaching speaking for the tenth grade students in MAN Pinrang in academic year 2018/2019 were effective. Key Words: group discussion, technique, students, speaking ability.